Securing the exception through securitization: Turkish modular emergency in the making. Issue 3 (3rd April 2023) - Kaliber, Alper
ABSTRACT: This study argues that the Schmittian exceptionalist view drawing on the norm/exception dichotomy is ill-equipped to grasp the nature and operation of current modular emergency regimes where normalcy and emergency coexist as different, yet intertwined modes of governance. These regimes are modular as they enable the interchangeable and simultaneous use of ordinary and extraordinary powers and legislation by executives. In modular emergencies, securitization plays a key role to create a "strategic ambiguity" where the distinction between the "normal" and the "exceptional" becomes untenable and invisible. In securitized political environments, it becomes increasingly difficult for societies to gauge if expanded executive powers and exceptionalist practices are justifiable, reasonable and proportional. Turkey was ruled under a nationwide state of emergency (SoE) for two years declared on 20 July 2016 soon after a failed coup attempt against the Turkish government. Even though the SoE was formally lifted in July 2018, the emergency powers and exceptionalist practices have become entrenched and institutionalized under the guise of the "presidential system of government" designed as a rule of modular emergency.